Polish Independent Press Review, no. 1 (1989) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Topical reviews of Polish samizdat publications in English prepared by RFE staff members to be used by different national broadcasting units. PIPR was published from 1986 until November 1989 as a continuation of Polish Underground Extracts (PUE). The Baltic Area and the Polish Independent Press / by Anna PomianAlthough the recent developments in the Baltic republics have been covered extensively in the Polish independent press during the last year, there has been little analytical comment on their significance. Coverage of Armenia by the Independent Press Continues / by Anna PomianFor the last year, the independent press in Poland has given regular coverage to events in Armenia; and the Polish opposition has recently extended practical support to the Armenian people. Wałęsa Warned against Alienating Radical Youth / by Anna PomianAlthough Solidarity has dissociated itself from the recent violent protests by young people, several independent publications have warned Wałesa of the risks involved in distancing himself from the younger generation. Police Officer Interviewed by Independent Press / by Anna PomianA Polish officer of the Civic Militia recently gave a detailed account of his working conditions in an interview with an independent publication. Profiles of Major Independent Polish Publications: "RIS - Regionalny Informator Solldarności Śląsko-Dąbrowskiej" / by Witold Pronobis"RIS - Regionalny Informator Solidarności Śląsko-Dąbrowskiej" was a biweekly and later a monthly bulletin published in Katowice from January 1982 until October 1988.